A case of burn evisceration with full-thickness injury to abdominal wall, bowel, bladder, and three extremities - Davit Shahmanyan; Matthew T. Joy; Bryan R. Collier; Emily R. Faulks; Mark E. Hamill (Surgical Case Reports)
Abstract Background Severe electrical burns are a rare cause of admission to major burn centers. Incidence of electrical injury causing full-thickness injury to viscera is an increasingly scarce, but severe presentation requiring rapid intervention. We report one of few cases of a patient with full-thickness electrical injury to the abdominal wall, bowel, and bladder. Case report The patient, a 22-year-old male, was transferred to our institution from his local hospital after sustaining a suspected electrical burn. On arrival the patient was noted to have severe burn injuries to the lower abdominal wall with evisceration of multiple loops of burned small bowel as well as burns to the groin, left upper, and bilateral lower extremities. In the trauma bay, primary and secondary surveys were completed, and the patient was taken for CT imaging and then emergently to the operating room. On exploration, the patient had massive full-thickness burns to the lower abdominal wall, five full-thickness burns to small bowel, and intraperitoneal bladder rupture secondary to full-thickness burn. The patient underwent damage-control laparotomy including enterectomies, debridement of bladder coagulative necrosis, and layered closure of bladder injury followed by temporary abdominal closure with vacuum dressing. The patient also underwent right leg escharotomy and partial right foot fasciotomies. The patient was subsequently transferred to the nearest burn center for continued resuscitation and comprehensive burn care. Conclusion Severe electrical burns can be associated with devastating visceral injuries in rare cases. Though uncommon, these injuries are associated with very high mortality rates. The authors assert that rapid evaluation and initial stabilization following ATLS guidelines, damage-control laparotomy, and goal-directed resuscitation in concert with transfer to a major burn center are essential in effecting a successful outcome in these challenging cases.